2019
DOI: 10.1001/jamanetworkopen.2019.14977
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Intranasal vs Intramuscular Naloxone on Opioid Overdose

Abstract: This randomized clinical trial compares 2 administration methods for the opioid antagonist naloxone in individuals served by a medically supervised drug-injecting facility in Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 36 publications
2
29
0
2
Order By: Relevance
“… 9 Despite the advantages of intranasal naloxone and its endorsement in current guidelines, 7 a recent clinical trial conducted in a supervised injection facility demonstrated greater efficacy of intramuscular naloxone over intranasal when the 2 medications were provided at equal doses in the same concentration. 10 …”
Section: Discussionmentioning
confidence: 99%
“… 9 Despite the advantages of intranasal naloxone and its endorsement in current guidelines, 7 a recent clinical trial conducted in a supervised injection facility demonstrated greater efficacy of intramuscular naloxone over intranasal when the 2 medications were provided at equal doses in the same concentration. 10 …”
Section: Discussionmentioning
confidence: 99%
“…The comparator dose of 0.8 mg intramuscularly was also used in a recent clinical trial of overdoses in an Australian safe injection Open access facility. 9 An advisory committee to the the US Food and Drug Administration has advised that a dose above 0.4 mg is the most appropriate comparator. 25 The WHO recommends intramuscular doses not to exceed 0.8 mg as the first dose in community overdose.…”
Section: Route Of Administration Concentration and Dosementioning
confidence: 99%
“…Open access are needed to deliver a therapeutic dose. Despite these shortcomings, epidemiological studies 5 and a few clinical trials [6][7][8][9] have shown promising results of such improvised IN naloxone. The WHO pointed out the low evidence behind many nasal sprays used in naloxone programmes and called for clinical trials on this crucial issue.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, avoidance of the gastrointestinal tract and hepatic metabolic breakdown increases drug availability [15]. IN administration has been explored with drug formulation design for the treatment of conditions other than anaphylaxis, including pain (opioids), heroin overdose reversal (opioid antagonists), Alzheimer's disease, and seizures (benzodiazepines) [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%